Family, Death and Afterlife According to Mosaics of the Abgar Royal Period in the Region of Osroene - SALMAN, Barış (Journal of Mosaic Research, 2009)
The region Osroene is the area including Edessa (Şanlıurfa), Carrhae (Harran) and Birtha (Birecik) located east of the Euphrates River. The Abgar Dynasty, the major power in the region, overthrew Seleukos’ control and regained independence in the region in 132B.C. Family members depicted together and at ease in mosaics of the royal period symbolize the importance of peace within the family and family unity. Of the figures portrayed next to the genearch, the wife is the most striking individual with her dignified pose. Family mosaics indicate that whole family will be together after death as they were in life. A Phoenix and two Orpheus mosaics found in the region also support the pagan notion of a new life after death.
p. 103-115, 2 ill. n.b. et 10 coul
Keywords: Bibliographie par pays, région ou ensemble géographique; Abgar (royaume); Aristocratie, aristocratique; Iconographie; Iconologie; Orphée; Phénix; Portrait en mosaïque; Portrait féminin; Séleucides; Birecik; Édesse; Euphrate; Harran, Carrhes; Osroène